THE ROLE OF SOVEREIGN DEBT IN SHAPING ECONOMIC POLICY - Kumar, Suresh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sovereign debt plays a crucial role in shaping the economic policies of nations, particularly in managing fiscal deficits and financing developmental projects. When a government borrows, it raises capital to fund public services, infrastructure, social programs, or stimulus measures during economic downturns. While sovereign debt enables growth and investment, its management is critical, as excessive borrowing can lead to unsustainable debt levels, jeopardizing economic stability. The role of sovereign debt in economic policy is multifaceted, involving the delicate balance between leveraging debt for growth and maintaining fiscal sustainability. Countries with high levels of sovereign debt face the challenge of ensuring that borrowing does not outpace the ability to repay. Debt management decisions, including the choice of borrowing sources, debt maturity, and currency risk, directly influence national fiscal policies, credit ratings, and macroeconomic stability. Sovereign debt influences inflation, interest rates, exchange rates, and social programs, as governments may implement austerity measures to reduce deficits or attract foreign investment. In times of economic crisis, sovereign debt becomes even more pivotal. For instance, during the 1991 economic crisis in India, high external debt led to balance of payments issues, triggering a series of reforms including IMF support and structural adjustments. Similarly, during the COVID-19 pandemic, India’s sovereign debt increased due to large stimulus packages, raising concerns over long-term fiscal health while aiming to sustain economic recovery. Ultimately, sovereign debt not only serves as a financing tool but also serves as a key determinant in crafting fiscal and monetary policies. The management of sovereign debt is therefore central to a country's economic strategy, influencing both short-term stability and long-term development.